Electrocatalytically driven fast removal of moisture by condensation of vapor and water splitting. (July 2019) - Lee, Tae Won; Kim, Hee Jun; Park, Jang Su; Baik, Jeong Min
Abstract: In this paper, an electrocatalytically driven fast removal of moisture adsorbed onto the surface to the air is described. It is a two-electrode electrochemical cell based on the nickel-copper-phosphide film as a biofunctional catalyst. The overpotentials for HER and OER are significantly reduced by the Cu incorporation to the nickel-phosphide, ascribed to the low charge transfer resistance. The long-term stability at high voltage (>10 V) is also obtained by introducing an oxygen-rich layer in the near-surface region of the film in the OER electrode. The devices are proven to remove water (pH 7.0) with a rate of approximately 0.6 ml/h at 10 V, reducing the water content in the air. A flexible cell with transparency over 90% is also fabricated and the water removal capability is found to maintain over 75% at a curvature of 0.18/cm. Graphical abstract: A facile strategy to fabricate the two-electrode electrochemical cell for the electrocatalytically driven moisture control technology, based on the nickel-copper-phosphide film, is demonstrated. It shows excellent water removal capability with a rate of 0.6 ml/h at 10 V, proven to be effective in removing the water adsorbed onto the surface, that is, controlling the water content in air. A flexible cell with transparency over 90% is also fabricated, which maintains the water removal capability over 75% at a curvature of 0.18/cm. Image 1 Highlights: A facile strategy to fabricate the electrochemical cell for moisture control, based on the nickel-copper-phosphide film, is demonstrated. This technology can control the content of the water in the air, that is, the humidity for a long time. It achieves long-term stability at high voltages using insertion of oxygen-rich layer in near-surface region of the film for OER. The water condensed onto the surface of the headlamp became quite clean within several minutes. A flexible cell with transparency over 90% maintained over 75% of the water removal capability at a curvature of 0.18/cm.